(untitled) (Damascus University Journal for legal sciences, 2025)
The Islamic law legalized to act with surmising after the impossibilty of acting with certainity to avoid the hardship , harassment and for the sake people; or else they fell in hard charge which is prohibited in our Islamic law. The project of acting with surmising manifsted in the Holy Quran and prophetic sunna. I have followed the extrapolated curriculum through. Then I have followed the comparative analytical curriculum among the four juristic doctrines in studying the juristic issues that relate to surmising. The research talked about the concept of surmising , then words related to it, and also it mentioned the instrument of acting with surmising within the holy Quran and prophetic sunna, after that it mentioned the applcations of surmising within the related rules , such as the surmising in the rule of the hardship brings facilitation, and also the surmising in the rule of certainity never be abolished by scepticism , and the surmising in the discordance between the apparent and the origin. The research came with introduction and two sections. So the introduction is (based prefaces) , it talked about the certainity of surmising and some words related to it. Conclusion: with main results and the recommendations. The main results: 1- surmising is due to scepticism that one of its sides be overbalanced after the impossibilty of acting with certainity. 2- the power of acting with the juristic rule and its branches comes from the Holy Quran and prophetic sunna. 3- the impact of surmising in the juristic issues let us consider in judging the issue according to the surmiser and the target of his mighty God Allah destination. 4- acting with surmising let us avoid the hardship and harassment from the charged, it became mean to attain sharia destination in keeping the religion, self, mind and ancestry. The jurists imposed juristic rules for the abundance of juristic issues, and its relating with scpticism. to control such juristic issues within rules such as the rule of the hardship brings facilitation with its branches: requisiteness is as necessity special or public, and the necessity is valuated by its value. And the rule of the certainity can not be abolished by scepticism, and its branches such as the rule of origin be remained what was stay as been, and also the surmising remained acting , but some t attain the sharia destination to keep up religion, self, mind, offsprings and money, and also as an instrument to achieve the sake of people wordly and afterlife. The recommendations: - to amblify in studying the juristic rules relating to surmising and all branches. - A comparative studying within juristic issues among surmising, delusion and scepticism.